2018
DOI: 10.1177/1937586718779360
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of a Dual Occupancy Neonatal Intensive Care Unit on Staff Workflow, Activity, and Their Perceptions

Abstract: In 2012, a tertiary neonatal intensive care unit (NICU) transitioned from an open plan (OP) to a dual occupancy (DO) NICU. The DO design aimed to provide a developmental appropriate, family-centered environment for neonates and their families. During planning, staff questioned the impact DO would have on staff workflow and activity. To explore the impact of changing from an OP to a DO NICU, a prospective longitudinal study was undertaken from 2011 to 2014, using observational, time and motion, and surveys meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Many of the publications in our sample, however, used complimentary data collection methods, such as interview or questionnaire, to supplement and enhance their observation (see right-hand column Table 2). Some of the studies which produced nonspecific findings from their observation data were able to draw more specific conclusions once these findings were merged with results from other data collection methods (Johnson & Delaney, 2006; Macdonald et al, 2012), especially where mixed methods were used (Anåker et al, 2018; Broom et al, 2019; McLaughlan et al, 2019; Shepley, 2002). For example, McLaughlan et al used surveys, drawings, and photo-elicitation interviews to complement spatial observation methods in their study of children’s behavior in waiting areas of a pediatric hospital (2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the publications in our sample, however, used complimentary data collection methods, such as interview or questionnaire, to supplement and enhance their observation (see right-hand column Table 2). Some of the studies which produced nonspecific findings from their observation data were able to draw more specific conclusions once these findings were merged with results from other data collection methods (Johnson & Delaney, 2006; Macdonald et al, 2012), especially where mixed methods were used (Anåker et al, 2018; Broom et al, 2019; McLaughlan et al, 2019; Shepley, 2002). For example, McLaughlan et al used surveys, drawings, and photo-elicitation interviews to complement spatial observation methods in their study of children’s behavior in waiting areas of a pediatric hospital (2019).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in an ethnographic study of the places that people occupy throughout their cancer care trajectory, Hughes observed participants continuously, for many hours across multiple inpatient and outpatient visits from diagnosis to end-of-life, and recorded detailed field notes about her impressions of the environment and all aspects of the participant’s behavior (Hughes et al, 2017). However, quantitative data were collected in 28% of the studies that utilized continuous observation ( n = 15), most often via a structured data collection form like that employed in snapshot methods, but with data recorded on the form throughout the observation period, rather than at intervals (Broom et al, 2019; Brown et al, 1997; Cloutman-Green et al, 2014; Gharaveis et al, 2020; Lim et al, 2020; Maben et al, 2016; Mazzei et al, 2014; Nanda et al, 2012; Pachilova & Sailer, 2020; Rashid et al, 2016; Shepley, 2002; Zadeh et al, 2014). For example, in a study of how spatial planning impacts visibility and staff communication in an emergency department, the frequency and duration of face-to-face communication between staff was recorded on a form continuously over multiple hours and compared across four hospitals with different floor plans and levels of visibility (Gharaveis et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An Australian study exploring the experience of staff and families in a redesigned unit, found dual occupancy pods maintained patient confidentiality and supported more effective communication between staff and families when compared to an open unit design. 34 Further exploration of the impact of unit design on FCC practices in Australia is warranted. The perception of peer support towards skin to skin presented the lowest level of agreement for participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the critical need for understanding the complexity of care delivered in Level I trauma rooms, a limited number of studies have examined the impact of the physical environment on disruptions to the workflow in the context of trauma rooms that jeopardize care (Ahmad et al , 2016; Bayramzadeh et al , 2018a; Bayramzadeh et al , 2021b; Cohen et al , 2016; Frellesen et al , 2015; Joseph et al , 2019; Neyens et al , 2019; Palmer et al , 2013; Stahl et al , 2006). Existing literature is primarily focused on investigating workflow disruptions and their relationship between the physical environment and team performance within the operating rooms (ORs) and intensive care units (ICUs) and neonatal intensive care units (Broom et al , 2019; Doede et al , 2018). Although similar, the unpredictable nature of trauma rooms is unique and requires a new lens for examination.…”
Section: Introductionmentioning
confidence: 99%